2020
DOI: 10.1016/j.clae.2020.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Changes in accommodative micro-fluctuations after wearing contact lenses of different optical designs

Abstract: A B S T R A C TPurpose: Accommodative micro-fluctuations (AMF) are small dioptric changes during accommodation. The aim of this study was to evaluate and compare changes in AMF when wearing silicone hydrogel contact lenses of two different optical designs. Methods: A multi-centre, randomised, cross-over, non-dispensing study was conducted on 68 adapted contact lens wearers aged 25-35 years to compare AMF responses to a spherical and aspheric silicone hydrogel (comfilcon A) lens designs. A Righton Speedy "i" se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Another investigation compared a spherical SV contact lens to a ‘multiple aspheric curve design’ in myopic adults aged 20–35 years and found a lower change in accommodative microfluctuations in the novel lens after a 20‐min reading task. This was described as an ‘objective measure of eye strain’ 38 …”
Section: Discussionmentioning
confidence: 99%
“…Another investigation compared a spherical SV contact lens to a ‘multiple aspheric curve design’ in myopic adults aged 20–35 years and found a lower change in accommodative microfluctuations in the novel lens after a 20‐min reading task. This was described as an ‘objective measure of eye strain’ 38 …”
Section: Discussionmentioning
confidence: 99%
“…One potential explanation for this result may be related to changes in accommodation stemming from the additional optical power of the lens: as is known, small dioptric changes in the so-called accommodative micro-fluctuations (AMF) during the accommodation process results in continued eye stress. This was used by Kajita et al [ 44 ], who compared spherical lenses with aspherical lenses via AMF variation during screen reading and confirmed that the aspheric lens design reduced ciliary muscle stress. Hence, the lens’s design was able to diminish regulatory muscle activity, leading in turn to reduced eye tiredness.…”
Section: Discussionmentioning
confidence: 99%
“…The ACOMOREF 2 (Righton, Japan) with AMF mode was used to record the MFs outcomes in this study [15]. It is an infrared optometer with a spectral power calculation to analyze and record the non-stationary spectrum of MF.…”
Section: Accommodative Micro-uctuationmentioning
confidence: 99%
“…Moreover, one previous study showed that high-frequency (1.3 to 2.2 Hz) of MFs represent tension of the ciliary muscle, that is, when the ciliary muscle contraction load increases, the HFC increases [14]. The ACOMEREF refractometer (Righton, Japan), which uses infrared light to record the HFC of MFs under different accommodative stimuli, has been proven to be useful to objectively evaluate the stress of the ciliary muscle [15].…”
Section: Introductionmentioning
confidence: 99%